Viral video in Malaysia - Rosde, Zulhilmi; A.Manaf, Aini Maznina (IIUM Press, 2017)
The emergence of Web 2.0 allows user to share information online. Since then, the world has been introduced to YouTube. YouTube is a video sharing website where people can upload videos and comments on the video. YouTube has been popular among people as it becomes a platform where they can promote themselves as well as spreading information on certain issues, or for entertainment. Ever since, the number of viral video is on the rise. Viral videos gain popularity and influential as one of the preferred methods in sharing information online. The question is what makes videos become viral especially in Malaysia? This paper attempts to answer questions about what viral video is, how viral video develops, and more importantly is how viral videos take place in Malaysia. Additionally, a closer look at how Islam addresses the issue of viral video is also discussed in the paper.